Supramolecular Assemblies from Poly(styrene)-block-poly(4-vinylpyridine) Diblock Copolymers Mixed with 6-Hydroxy-2-naphthoic Acid - Bharatiya, Bhavesh; Schumers, Jean-Marc; Poggi, Elio; Gohy, Jean-François (Polymers, 2013)
Supramolecular assemblies involving interaction of a small organic molecule, 2-hydroxy-6-Naphthoic acid (HNA), with poly(styrene)-block-poly(4-vinylpyridine) (PS-b-P4VP) diblock copolymers are utilized to obtain micellar structures in solution, nanostructured thin films on flat substrates and, finally, nanoporous thin films. The formation of hydrogen bonds between HNA and the poly(4-vinylpyridine) (P4VP) blocks is confirmed by spectroscopic measurements. The accordingly P4VP/HNA hydrogen-bonded complexes are poorly soluble in 1,4-dioxane, resulting in the formation of micellar structures with a P4VP/HNA core and a polystyrene (PS) corona. Those micelles have been spin-coated onto silicon wafers, resulting in nanostructured thin films consisting of P4VP/HNA dot-like features embedded in a PS matrix. The morphology of those films has been tuned by solvent annealing. Selective dissolution of HNA by methanol results in the formation of a nanoporous thin film. The P4VP/HNA nanodomains have been also cross-linked by borax, and the thin films have been further dissolved in a good solvent for PS, leading to micelles with a structure reminiscent of the thin films.